ANALYSIS IMPLEMENTATION DEVELOPMENT SPORTS EDUCATION SPORTS ACHIEVEMENT RECREATIONAL SPORTS - Ahmad Zulyaden; Rahma Dewi; Afri Tantri (Universitas Negeri Medan, 2022)
This article discusses the analysis of the implementation of the development of educational sports, achievement sports, recreational sports, and sports with disabilities, all sports activities in Indonesia must be in line with all the rules contained in Law no. 3, Th. 2005, SKN. The Indonesian people hope that the presence of Law no. 3, Th. 2005, SKN as a legal umbrella that protects and guides all sporting activities will bring changes for the better, which can raise the dignity of the Indonesian nation in the eyes of the world. In its implementation, Law No. 3 SKN brings positive and negative impacts on developments in the main sports organizations and sports in Indonesia, namely in educational sports, achievement sports, recreational sports. The support of the entire Indonesian nation from the regional to the central level, especially sports players, namely athletes, sports coaches, and sports personnel is highly expected for the success of enforcing Law no. 3, Th. 2005, SKN.Keywords: Implementation, Analysis Development, Sports Education, Sports Achievement, Recreational Sports.